2022
DOI: 10.21203/rs.3.rs-994599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the Epidemiology of STDs in China: Based on the GM (1,1) Model

Abstract: Background: It has been reported that COVID-19 pandemic has greatly impacted on the epidemiological trend of Sexually Transmitted Diseases (STDs) in many countries. However, relevant researches are limited in China. We aimed to analyze the extent of COVID-19 pandemic impact on STDs in China.Methods: The incidence of HIV infection, syphilis and gonorrhea in China from 2008 to 2020 was collected. But only data of these three STDs from 2013 to 2018 were used to establish the Grey Model (1,1) considering about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Previous studies [8][9][10]24,31 found that the incidence of STDs decreased dramatically in 2020, which was also found in our research. The IRRs of the five STDs were significantly below one in 2020 compared with 2019, but there was no statistical significance for the IRRs of hepatitis B, hepatitis C, and gonorrhoea in 2021 (Table 4).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies [8][9][10]24,31 found that the incidence of STDs decreased dramatically in 2020, which was also found in our research. The IRRs of the five STDs were significantly below one in 2020 compared with 2019, but there was no statistical significance for the IRRs of hepatitis B, hepatitis C, and gonorrhoea in 2021 (Table 4).…”
Section: Discussionsupporting
confidence: 90%
“…The IRRs of the five STDs were significantly below one in 2020 compared with 2019, but there was no statistical significance for the IRRs of hepatitis B, hepatitis C, and gonorrhoea in 2021 (Table 4). Many studies 11,13,24 have reported the recovery of the incidence rates for infectious diseases when NPIs were relaxed, and our research also observed three STD incidence levels (hepatitis B, hepatitis C, and gonorrhoea) return to pre-COVID-19 levels. The recovery of the gonorrhoea incidence level was relatively quick compared to the other four STDs, which could be explained by the shorter incubation period (1-14 days) and obvious clinical symptoms when present.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation